Influence of Different Factors of Crumb Rubber on the Properties of Crumb Rubber Modified Asphalt - Liu, Shengjie (Asian Journal of Chemistry, 2012)
Over the years, the waste tires have become a serious environment problem and using the tire rubber in asphaltic concrete mixtures as additives is an effective way to dispose them, The former researches had found that the application of crumb rubber in asphalt binder can improve the binder properties. This research intends to investigate the effect factors of crumb rubber modifier binder in the laboratory. For this study, the crumb rubber modifier binder was produced by the different blending temperatures (160, 180, 200 and 220 ºC), different crumb rubber mesh (40, 60, 80, 100) and different crumb rubber contents (15, 20, 25 and 30 % by weight of asphalt binder). Results observed from this study indicates: (1) the blending temperatures, crumb rubber mesh and crumb rubber contents have great influence on the binder properties; (2) the effect factors exist their optimal ranges, which are thought to be due to the effect factors have different influence on the binder absorption. (3) the optimal ranges about blending temperatures, crumb rubber mesh and crumb rubber contents in this study are 180 ºC, 60 mesh and 25 % by weight, respectively.